2018
DOI: 10.3390/nu10111680
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Dioscorea batatas Flesh and Peel Extracts against Ethanol-Induced Gastric Ulcer in Mice

Abstract: Gastric ulcer is a major digestive disorder and provoked by multifactorial etiologies, including excessive alcohol consumption. In this study, we examined the gastroprotective effect of aqueous and ethanolic extracts of Dioscorea batatas Decne (DBD; commonly called Chinese yam) flesh or peel against acidified ethanol-induced acute gastric damage in mice. Our findings demonstrated that oral supplementation of aqueous or ethanolic extracts of DBD flesh or peel before ulcer induction was significantly effective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 42 publications
4
24
0
Order By: Relevance
“…It is well established that PGE 2 is beneficial for duodenal ulcer healing wherein it acts as an important agent in gastrointestinal mucosal defense [32]. Furthermore, PGE 2 is an efficacious vasodilator which promotes ulcer healing by enhancing the release of mucus and bicarbonate and inhibiting the gastric acid secretion [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that PGE 2 is beneficial for duodenal ulcer healing wherein it acts as an important agent in gastrointestinal mucosal defense [32]. Furthermore, PGE 2 is an efficacious vasodilator which promotes ulcer healing by enhancing the release of mucus and bicarbonate and inhibiting the gastric acid secretion [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its medicinal value is significant because it contains numerous bioactive constituents such as polysaccharides, allantoin, and polyphenols including flavonoids [3]. Previous studies have demonstrated that the Chinese yam exerts strong anti-oxidative [4], cholesterol-lowering [5], growth hormone-releasing activity [6], and protective effects against ethanol-induced gastric ulcers [7]. Recent studies have revealed intimate relations between bioactivities and their responsible secondary metabolites including allantoin, saponins and phenanthrenes.…”
Section: Introductionmentioning
confidence: 99%
“…Lung tissue homogenate was subjected to measurement of IL-10 (ELISA MAX standard set, Biolegend, San Diego, CA, USA) and prostaglandin E 2 (PGE 2 ) (Cayman Chemical, Ann Arbor, MI, USA) as per the manufacturer’s instructions. Liver tissue homogenate was used to determine the levels of 8-hydroxy-2′-deoxyguanosine (8-OHdG) (Cat # ADI-EKS-350; Enzo Life Sciences, Farmingdale, NY, USA) and malondialdehyde (MDA) (Cat # ALX-850-287; Enzo Life Sciences, Inc., Farmingdale, NY, USA) as previously described [ 34 ]. The obtained values were normalized to the total amount of proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Cytoplasmic and nuclear fractions of cultured cells and mouse tissues were prepared using the NE-PER Nuclear and Cytoplasmic Extraction Reagents (Thermo Fisher Scientific, Rockford, IL, USA). The proteins in each fraction were blotted and their relative expression levels were determined as previously described [ 34 , 35 ]. Briefly, the primary antibodies used in this study were immunoglobulins against COX-2 (Cell Signaling Technology, Danvers, MA, USA), NF - κB (Bioworld Technology, St. Luis.…”
Section: Methodsmentioning
confidence: 99%